Mobility and Noise Pollution. Noise-reduction Traditional Strategies and Green Mobility Ones - Gargiulo, Carmela; Romano, Rosario Aniello (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The urbanized territories are quite complex environments in many ways, whose management requires, on the one hand, adequate skills to mediate among the different needs, often conflicting, and on the other hand a clear idea of the target to hit. One of these aspects is the need to ensure mobility in urban areas and, simultaneously, reduce noise levels below the values that are compatible with the well-being of citizens. There are several sources of noise in an urban context such as vehicle and rail traffic, the fixed sound sources due to craft and trade activities, as well as to equipment for buildings, to human activities related to recreation and tourism. It must be emphasized, however, that not all noise content has a negative value but there are noise sources such as the noise produced by the local markets and/or that produced by craft activities with historical value, the noise, or rather, the sounds perceived in public parks, town centres and/or areas on the sea which, on the contrary, have a positive value. They represent, in fact, the set of sounds that contribute to the perception of the “soundscape” of an area, which are to be preserved as they are not only appreciated but also sought after by citizens. The noise generated by vehicle traffic, however, while not disregarding the contribution to noise pollution produced by other infrastructure for mobility in urban area, represents one of the major contributor to the noise levels recorded in urban areas, disturbing, firstly, people exposed to it and, secondly, masking the perception of pleasant sounds by altering the “soundscape” of the area. In this context, strategies and interventions to reduce noise caused by road traffic, both the traditional ones (regulations on vehicles, circulation, road, city planning) and the new ones related to green mobility, have a twofold purpose as they not only reduce the amount of noise generated by road traffic, but at the same time, help to bring out the positive noise typical of the “soundscape” of the considered urban context. The article is divided into four sections: the first, edited by C. Gargiulo, briefly explains the situation in Italy and Europe, also through the help of several reports on the subject; the second, edited by R. Romano, illustrates in a comprehensive way the main Italian and EU legal regulations; the third, edited by R. Romano, describes measures and specific interventions for reducing environmental noise in urban areas in the awareness that noise control may be better controlled by intervening on the sound source rather than on the receiver; finally, the fourth, edited by C. Gargiulo, proposes the development of strategies for reducing vehicle traffic noise in urban areas, which, in accordance with the directions of Community, prefer the integration and harmonization of noise protection requirements and of the aspects associated to urban and regional planning and governance of mobility.